The Role of Students in Increasing the Interest of Sungai Baung Village Children in Sports - Hendra Taufik; Putri Patricia Ningrum Ginting; Rahmi Alfina; Harimbi Okta Dwianti; Dewi Lukluum Maknun; Beny Kesuma; Ikhsan Mulya; Putri Sekar Arum Pujiati; Alif Rasyidin Ali; Kayla Shafa Raudina; Nadatha Fanindhiya Putri (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this community service is to discover the extent of students' interest in sports activities. Through questionnaires, the needs and improvements needed for these students' sports education may be seen. Lack of special attention within SDN 011 Sungai Baung and SDN 022 Titian Tinggi on the students' interest's guidance specifically on sports has motivated the initialization of this research with the purpose of optimizing non- academics potentials. This research will be conducted using quantitative and Joyful Learning methods where the samples are taken from the students of SDN 011 Sungai Baung and SDN 022 Titian Tinggi. Those students will be observed specifically within the scope of sports activities in order to see the correlation of academics' role in influencing the students' interest in sports. The results showed that the role of Riau University students was quite capable of increasing students’ interest in sports by 19%.